2019
DOI: 10.1002/anie.201811593
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐Locked Tetrathienylethene as a Building Block for Hole‐Transporting Materials: Toward Efficient and Stable Perovskite Solar Cells

Abstract: The construction of state‐of‐the‐art hole‐transporting materials (HTMs) is challenging regarding the appropriate molecular configuration for simultaneously achieving high morphology uniformity and charge mobility, especially because of the lack of appropriate building blocks. Herein a semi‐locked tetrathienylethene (TTE) serves as a promising building block for HTMs by fine‐tuning molecular planarity. Upon incorporation of four triphenylamine groups, the resulting TTE represents the first hybrid orthogonal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
111
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(116 citation statements)
references
References 49 publications
3
111
0
Order By: Relevance
“…However, the complicated synthesis procedures and low yield of Spiro‐OMeTAD make its price very expensive, triggering the researchers over the world to search for/develop efficient and low‐cost alternative HTMs. To date, many alternative HTMs constructed with different conjugated core units, such as phenothiazine, thiophene, phenoxazine, silolothiophene, triazines, and tetraphenylethene, have been reported . Benzotriazole (BTA) is a cheap and commercially available material, which has been widely used in designing sensitizers for dye‐sensitized solar cells by reason of the outstanding electron‐accepting property.…”
Section: Summary Of Optical and Electrochemical Properties Of 2fbta‐1mentioning
confidence: 99%
“…However, the complicated synthesis procedures and low yield of Spiro‐OMeTAD make its price very expensive, triggering the researchers over the world to search for/develop efficient and low‐cost alternative HTMs. To date, many alternative HTMs constructed with different conjugated core units, such as phenothiazine, thiophene, phenoxazine, silolothiophene, triazines, and tetraphenylethene, have been reported . Benzotriazole (BTA) is a cheap and commercially available material, which has been widely used in designing sensitizers for dye‐sensitized solar cells by reason of the outstanding electron‐accepting property.…”
Section: Summary Of Optical and Electrochemical Properties Of 2fbta‐1mentioning
confidence: 99%
“…Hole‐transport materials (HTMs) play an important role in facilitating the transportation of holes from perovskite to the corresponding electrode, and a lot of molecule dopant‐free HTMs have been reported to surpass the high cost and the instability issues of 2,2′,7,7′‐tetrakis( N,N ‐di‐ p ‐methoxyphenylamino)‐9,9′‐spirobifluorene (spiro‐OMeTAD) and poly(bis(4‐phenyl)(2,4,6‐trimethylphenyl)amine) (PTAA), arising from the synthetic complexity and dopants, which are the most widely used and successful HTMs until now . Zhu et al reported a semilocked tetrathienylethene‐containing molecule dopant‐free HTM for the n–i–p pero‐SCs, and the PCE of the best device reached 20% . The highest PCE of the n–i–p pero‐SCs based on molecule dopant‐free HTMs is 21%, achieved by dithieno[3,2 ‐b :2′,3′‐ d ]pyrrol‐cored HTM .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] However,t heir commercialization is still ac hallenge by poor thermal and/or moisture stability in spite of great progresses in either setting blocking layers at interfaces or developing new encapsulation techniques. [6,7] Under longterm illumination and heat attack, the ion migration behavior in hybrid devices is arguable and difficult to completely avoid. [8] Aiming for improved stability,all-inorganic (CsPbX 3 , X = I À ,B r À ,o rC l À )p erovskites free of volatile components by replacing the organic MA + or FA + species with inorganic Cs + have been widely studied for alternative light absorbers.…”
mentioning
confidence: 99%